Prevalence of HIV, HCV and sexually transmitted infections among injecting drug users in Rawalpindi and Abbottabad, Pakistan: evidence for an emerging injection-related HIV epidemic. (23rd March 2009) - Platt, L; Vickerman, P; Collumbien, M; Hasan, S; Lalji, N; Mayhew, S; Muzaffar, R; Andreasen, A; Hawkes, S
Abstract : Objectives: To measure the prevalence of hepatitis C virus (HCV), HIV and sexually transmitted infections (STI) among injecting drug users (IDUs) in Rawalpindi and Abbottabad and to examine risk factors associated with HIV and HCV. Methods: Two cross-sectional surveys were performed of community-recruited IDUs with collection of clinical specimens for testing of HCV, HIV and other STIs. Behavioural data were collected through interviewer-administered questionnaires. Characteristics and risk behaviours were compared across cities. Univariate and multivariate analyses explored risk factors associated with HIV and HCV. Results: The prevalence of HIV was 2.6% (95% CI 0.83% to 4.5%) in Rawalpindi (n = 302) and zero in Abbottabad (n = 102). The prevalence of HCV was significantly higher in Rawalpindi at 17.3% (95% CI 13.0% to 21.6%) than in Abbottabad at 8% (95% CI 2.6% to 13.4%). The prevalence of other STIs was low in both cities, with <2% of participants having current gonorrhoea or Chlamydia and <3% with active syphilis. Injecting risk behaviours were greater in Rawalpindi. An increased risk of HCV was associated with using informal sources as a main source of new needles/syringes (OR 2.8, 95% CI 1.3 to 6.0) compared with pharmacies and a history of drug treatment (OR 3.7, 95% CI 0.9 to 11.6). Reporting symptoms of an STI was associated with decreased odds of HIV in Rawalpindi (OR 0.02, 95% CI 0.03 to 0.9). Conclusions: The findings suggest recent transmission of HIV and HCV and point to the urgent need for the provision of clean needles/syringes to IDUs and a review of how needles/syringes are currently provided via healthcare establishments.